The Application of Timing in Therapy of Children and Adults with Language Disorders - Szelag, Elzbieta; Dacewicz, Anna; Szymaszek, Aneta; Wolak, Tomasz; Senderski, Andrzej; Domitrz, Izabela; Oron, Anna (Frontiers in Psychology, 2015)
A number of evidence revealed a link between temporal information processing (TIP) and language. Both literature data and results of our studies indicated an overlapping of deficient TIP and disordered language, pointing to the existence of an association between these two functions. On this background the new approach is to apply such knowledge in therapy of patients suffering from language disorders. In two studies we asked the following questions: (1) can the temporal training reduce language deficits in aphasic patients (Study 1) or in children with specific language impairment (SLI, Study 2)? (2) can such training ameliorate also the other cognitive functions? Each of these studies employed pre-training assessment, training application, post-training and follow-up assessment. In Study 1 we tested 28 patients suffering from post-stroke aphasia. They were assigned either to the temporal training (Group A, n = 15) in milliseconds range, or to the non-temporal training (Group B, n = 13). Following the training we found only in Group A improved TIP, accompanied by a transfer of improvement to language and working memory functions. In Study 2 we tested 32 children aged from 5 to 8 years, affected by SLI who were classified into the temporal training (Group A, n = 17) or non-temporal training (Group B, n = 15). Group A underwent the multileveled audio-visual computer training Dr. Neuronowski®, recently developed in our laboratory. Group B performed the computer speech therapy exercises extended by playing computer games. Similarly as in Study 1, in Group A we found significant improvements of TIP, auditory comprehension and working memory. These results indicated benefits of temporal training for amelioration of language and other cognitive functions in both aphasic patients and children with SLI. The novel powerful therapy tools provide evidence for future promising clinical applications.